2020
DOI: 10.32674/jis.v10i4.1190
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Study of Lived Experiences of International Students in Turkey

Abstract: Internationalization trends in higher education have become a significantly accentuated issue and student mobility is considered as one of the core components of internationalization in higher education. This study focuses on investigating the lived experiences of international students at a state university in Turkey using qualitative research method and phenomenological design. The research data were collected through semi-structured interviews in order to reveal the participants’ experiences and their overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…It can be assumed that there are similarities between Indonesian and their home cultures since mostly they come from Africa, which adheres to a collective culture that emphasizes more on harmony. This result is in line with previous research which found that local culture and society facilitate the adaptation process of international students (Kılınç, Arslan, & Polat, 2020). The second mode is observation.…”
Section: Discussionsupporting
confidence: 92%
“…It can be assumed that there are similarities between Indonesian and their home cultures since mostly they come from Africa, which adheres to a collective culture that emphasizes more on harmony. This result is in line with previous research which found that local culture and society facilitate the adaptation process of international students (Kılınç, Arslan, & Polat, 2020). The second mode is observation.…”
Section: Discussionsupporting
confidence: 92%
“…Spencer-Oatey and Xiong (2006) also reveal that sojourning students are more likely to have depression symptoms because of challenges and difficulties integrating with the host culture and adjusting to new routines in their daily life. Furthermore, Kılınç, Arslan and Polat (2020) report that common challenges international students often face can fit in a wide range of sociocultural, psychological, financial and academic issues. According to Molinsky (2007), however, assuming international students overcome various challenges they experience, they could successfully adapt to their new surroundings and avoid the negative impacts of norms and stereotypes.…”
Section: Figure 1 the Number Of International Students In Turkish Heismentioning
confidence: 99%
“…These patterns have led to very few studies focused on the micro-level at individual institutions or on specific internationalization programs. Of the studies that examine specific internationalization business programs, few explore the perspective of students (Guillotin, 2018;James, 2018;Kilinc et al, 2020;Hosein et al, 2018;Moglen, 2017), and even fewer deal with the student experience in HE internationalization programs in China (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%